2021
DOI: 10.3390/su13052552
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint Comparative Analysis of Cardboard and Plastic Containers Used for the International Transport of Spanish Tomatoes

Abstract: Agricultural packaging has a direct impact on the environmental performance of food. The carbon footprint (CF) of two of the most used packaging systems for international transport by road of fruit and vegetables is assessed and compared. Corrugated cardboard boxes (CCB) and polypropylene foldable boxes (PPB) in two different sizes are the object of this study. For the reusable boxes, three different scenarios are considered regarding the number of uses of each box (20, 50, and 100 uses). Product CF ISO 14067:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, reusable agricultural packaging has additional challenges and potential impacts, which are returning the packages and cleaning them after each use. A study comparing single-use cardboard and polypropylene foldable boxes in fact concluded that the former had a lower carbon footprint than the latter [31].…”
Section: Energy Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, reusable agricultural packaging has additional challenges and potential impacts, which are returning the packages and cleaning them after each use. A study comparing single-use cardboard and polypropylene foldable boxes in fact concluded that the former had a lower carbon footprint than the latter [31].…”
Section: Energy Alternativesmentioning
confidence: 99%
“…The water consumption for cardboard production can be further reduced if the recycling rate of cardboard is upscaled to a higher percentage or a different, non-water using material is used. The choice of plastic-based reusable packaging could be an option, but it needs to be cleaned after every use and therefore consumes water in the process [31].…”
Section: Reducing Water Consumptionmentioning
confidence: 99%
“…Initially, a low range of standardized sizes was common in the industry, but nowadays, companies like Amazon have set what is called the “science of packaging”, by increasing the diversity of sizes, and therefore minimizing the usage of raw materials and optimizing transport. Cardboard is key in this configuration, due to its versatility, price compared with other alternatives and environmental footprint [ 4 , 7 ]. These cardboard boxes are designed not only by considering how various holes (to handle it) might affect the compressive strength but also taking into account how the vibrations during transportation might affect the products delivered [ 1 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also takes into account various other gaseous chemicals that can induce the greenhouse effect. Therefore, the carbon footprint is often defined as the sum of all emissions (and capture) of carbon dioxide and other GHGs for the particular life cycle of a given product, quantitatively expressed in CO 2 equivalent [5,6]. The carbon footprint is, therefore, an important tool based on LCA, which takes into account, among others, the category of global warming impact (or climate change, depending on the LCA method) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, for the sake of simplicity, the emissions per unit of load carried (e.g., per pallet or container) are taken into account [10]. In Spain, for example, national databases containing ecological factors are used for the different types of forklift truck drives [6]. More complex models attempt to explain the components of the total carbon footprint resulting from various operating statuses of the forklift trucks, such as the proportion of time spent working with and without a load, the FLT speed distribution, the frequency of acceleration, etc.…”
Section: Introductionmentioning
confidence: 99%